Comparison of Temperatures Measured with Thermal Infrared Imaging and Thermocouples in the Vacuum Cooling of Cut Rose (Rosa hybrida L. cv. First Red) - Song, Xiaoyong (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2010)
The temperature distributions of cut flowers under vacuum cooling are important to their vase life. In this work, the surface temperatures of the inner petal, outer petal, leaf and stem of cut rose (Rosa hybrida L. cv. First Red) were measured during the vacuum cooling process. Under a pressure reduction rate of 178.04 mbar min(-1), measurements were made by using a thermal infrared camera and thermocouples; the performance of the two methods was compared. The temperature profiles presented significant differences in average cooling rates of the different parts of the cut flower. For the petal, leaf and stem, the temperature distributions measured with a thermal infrared camera were non-uniform; the maximum temperature difference between the inner and the outer petal was 9.9 degrees C. Moreover, the average initial and final temperatures measured with a thermal infrared camera were 2.46 degrees C and 4.50 degrees C, respectively, lower than the values obtained with the use of thermocouples. These results indicate that thermal infrared imaging could measure the average temperature of an area, which is more representative, rather than just a single point (as detected by the thermocouple).